Science of genome - Cruz Cubas, Antonio (2002)
The limited success obtained in February 2001 in USA by two teams (public and private) for sequencing the human genome (estimated total size 3,2 gigabases) open a new and broad scientific field. This is the science of genomic, a discipline that will lead to changes in knowledge and methodologies in many areas like medicine, immunology, genetics, biochemistry and others. Some basic characteristics of our genome have been identified by the Human Genome Project and the more importants are: the coding regions of the human genome represent about 1% of full-length DNA.The present or past function of the incorrectly named “junk DNA” is as yet unknown. Our genes are composed of coding (exons) and no-coding (introns) regions. The latter are significatively larger in our species that in any other genome yet sequenced. The regions rich in G-C pairs are also those which have a higher gene density and correspond mainly to poorly stained bands of chromosomes observed by microscopy. Also, several interactions and supplementary regions are observed in human genome. For human medicine and immunology this scientific exploit is beneficial. One thousand and one hundred genes pathogens for man were discovered by 2000 and an estimated twenty thousand genes are responsible for the human normal and pathologic immune responses. Proteomics and transcriptomics are linked with the genome analysis and their importance is growing for the genomic science.